MIXING CODE IN SPEECH OF MEGAWATI SOEKARNO PUTRI IN CELEBRATION OF THE 50TH ANNIVERSARY OF PDI Perjuangan - Rahayu, Sri; Anggraini, Nori; Goziyah, Goziyah (Universitas Muhammadiyah Tangerang, 2023)
Based on the results of research on code mixing in Megawati Soekarnoputri's speech in commemoration of the PDI Perjuangan 50th Anniversary on 10 January 2023 in Jakarta, it can be concluded that Megawati Soekarnoputri often uses Javanese code mixing. This is because most members of the PDI Perjuangan sympathizers come from the area of Java Island or more precisely Central Java. It is hoped that code mixing by Megawati Soekarnoputri will result in active communication with her speech partners